2009
DOI: 10.2967/jnumed.108.061606
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pulmonary Embolism with Combined Ventilation–Perfusion SPECT and Low-Dose CT: Head-to-Head Comparison with Multidetector CT Angiography

Abstract: The diagnosis of pulmonary embolism (PE) is usually established by a combination of clinical assessment, D-dimer testing, and imaging with either pulmonary ventilation-perfusion (V/Q) scintigraphy or pulmonary multidetector CT (MDCT) angiography. Both V/Q SPECT and MDCT angiography seem to have high diagnostic accuracy. However, only limited data directly comparing these 2 modalities are available. Hybrid g-camera/MDCT systems have been introduced and allow simultaneous 3-dimensional lung V/Q SPECT and MDCT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
255
1
28

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(292 citation statements)
references
References 25 publications
6
255
1
28
Order By: Relevance
“…SPECT/CT versus CTPA comparison using the study by Gutte et al 14. imaging parameters, our findings demonstrate the total cost burden to be approximately 3.1 million USD for SPECT/CT versus 3.0 million USD for CTPA, leading to an additional PPPM of $3.8 million for SPECT/CT.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…SPECT/CT versus CTPA comparison using the study by Gutte et al 14. imaging parameters, our findings demonstrate the total cost burden to be approximately 3.1 million USD for SPECT/CT versus 3.0 million USD for CTPA, leading to an additional PPPM of $3.8 million for SPECT/CT.…”
Section: Resultsmentioning
confidence: 66%
“…To address some of the inherent limitations arising from using data from multiple studies that encompassed different settings of care (high volume vs. low volume), patient populations (clinical trial vs. retrospective analysis), a third scenario analysis was performed wherein SPECT/CT was explicitly compared to CTPA, the most commonly used imaging modality, the caveat being that the key imaging parameters—sensitivity (97% vs. 67.7%), specificity (100% for both) and nondiagnostic rates (0% for each)—would be derived from head‐to‐head studies alone 14. Similar to our study approach, these parameters would be required to be weighted by the studies’ sample sizes in case of multiple studies with the remaining parameters kept the same as in our base‐case analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…stratejiler önerilmiştir. Tek foton emisyon bilgisayarlı tomografi (SPECT) V/P ile toplanan multiplanar görün-tülerle tanısal olmayan tarama sıklığını azaltabileceği gösterilmiştir (17)(18)(19).…”
Section: Direkt Katater Pulmoner Anjiografiunclassified
“…In the PIOPED II study the positive predictive value for a PE within a lobar pulmonary artery was 97 % but fell to 68 % and 25 % at the segmental and subsegmental levels, respectively. Bajc et al and a prospective study by Gutte et al showed that V/P SPECT has higher sensitivity and specificity and less non-diagnostic findings than MDCT [10,14]. A recent study by Mahdavi et al showed that in the presence of an indeterminate CT angiography (CTA) in patients with high clinical suspicion of PE, V/P SPECT often provides a diagnosis [15].…”
Section: Comparison With Mdctmentioning
confidence: 99%